Impact of institute and person variables on teachers' conceptions of learning and teaching*. (3rd August 2015) - Jacobs, Johanna C.G.; Muijtjens, Arno M.M.; Van Luijk, Scheltus J.; Van Der Vleuten, Cees P.M.; Croiset, Gerda; Scheele, Fedde
Abstract: Background : Teachers' conceptions of learning and teaching are important for faculty development to result in enduring changes in teaching practices. Until now, studies on these conceptions have mostly focused on traditional, lecture-based curricula rather than on small-group student-centred educational formats, which are gaining ground worldwide. Aim : To explore which factors predict teachers' conceptions in student-centred curricula. Methods : In two Dutch medical schools with 10 and 40 years of student-centred education, teachers were asked to fill out the Conceptions of Learning and Teaching (COLT) Questionnaire to assess their 'teacher-centredness', 'appreciation of active learning' and 'orientation to professional practice'. Next, we quantitatively assessed the relations of teachers' conceptions with their personal and occupational characteristics and institute. Results : Overall response was 49.4% ( N = 319/646). Institute was the main predictor for variance in all three scales, and discipline, gender and teaching experience significantly explained variance in two of the scales. More than 80% of the variance was not explained by these factors. Conclusion : Longer exposure to a student-centred curriculum was associated with fewer teacher-centred conceptions, greater 'appreciation of active learning' and stronger 'orientation towards professional practice'. In line with studies on lecture-based curricula, discipline, gender and teaching experience also appeared important for teachers' conceptions in student-centred curricula. More research is necessary to better understand the influence of institute on the three teachers' conceptions scales.